Decreasing free fatty acid of crude palm oil with polyvinylidene fluoride hollow fiber membranes using a combination of chitosan and glutaraldehyde. Issue 35 (12th August 2022) - Widiastuti, Nurul; Silitonga, Romaya Sitha; Dharma, Hadi Nugraha Cipta; Jaafar, Juhana; Widyanto, Alvin Rahmad; Purwanto, Mochammad
Abstract : Crude palm oil (CPO) has emerged as a significant commodity in the economic and social development of producer nations. Abstract : Crude palm oil (CPO) has emerged as a significant commodity in the economic and social development of producer nations. However, the presence of free fatty acids (FFAs) results in decreased CPO quality. Due to many advantages, the PVDF hollow fiber membrane has a higher potential to remove FFA from CPO than other polymeric membranes, despite the fact that FFA rejection performance remains poor. To solve this issue, membrane surface modification has emerged as one of the potential options for increasing electrostatic contact between the membrane surface and the FFA, resulting in high efficiency FFA separation from CPO. In this investigation, the membrane surface was coated with chitosan (CS) as a coating agent and glutaraldehyde (GA) as a crosslinking agent. The findings of the characterization demonstrated that the presence of a CS/GA combination with a low CS weight on the membrane surface resulted in enhanced hydrophilicity, porosity, water flow, and surface roughness. Furthermore, as compared to the uncoated PVDF hollow fiber membrane, the performance of the CPO with PVDF/CS 0.5 hollow fiber membrane achieved a maximum result of FFA rejection of up to 14.99%. The use of a mixture of CS and GA on the PVDF membrane surface to improve FFA reduction has been shown to be a promising technique for scaling up membrane technology.